Answer:
a = 2, b = - 3, c = - 8
Step-by-step explanation:
Expand f(x) = a(x + b)² + c and compare coefficients of like terms, that is
a(x + b)² + c ← expand (x + b)² using FOIL
= a(x² + 2bx + b²) + c ← distribute parenthesis by a
= ax² + 2abx + ab² + c
Compare like terms with f(x) = 2x² - 12x + 10
Compare coefficients x² term
a = 2
Compare coefficients of x- term
2ab = - 12, substitute a = 2
2(2)b = - 12
4b = - 12 ( divide both sides by 4 )
b = - 3
Compare constant term
ab² + c = 10 , substitute a = 2, b = - 3
2(- 3)² + c = 10
18 + c = 10 ( subtract 18 from both sides )
c = - 8
Then a = 2, b = - 3, c = - 8
Answer:
I think after 1.6 s it Will catch the dog
Answer:
24
Step-by-step explanation:
from the question above,
30+(-6) =
when plus is multiplying minus it's minus
+ × - = -
30-6 = 24
Answer:
Infinitely many solutions.
Step-by-step explanation:
Let's solve your system by elimination.
x−3y=9;−x+3y=−9
x−3y=9
−x+3y=−9
Add these equations to eliminate x:
0=0
<u>Answer:</u>
Infinitely many solutions.